THE MECHANISM OF LANDSLIDE-INDUCED DEBRIS FLOW IN GEOTHERMAL AREA, BUKIT BARISAN MOUNTAINS OF SUMATRA, INDONESIA - wilopo, Wahyu; Faisal Fathani, Teuku (Journal of Applied Engineering Science, 2021)
Landslides frequently occur in Indonesia, especially in the geothermal areas located on Sumatra's mountainous island. On April 28, 2016, around 04:30 Western Indonesia Time, a landslide-induced debris flow occurred in Lebong District, Bengkulu Province, Indonesia. The source area of the landslide was located at Beriti Hill on the Bukit Barisan Mountain Range. It resulted in 6 fatalities and damage to infrastructures such as geothermal facilities, roads, water pipes, houses, and bridges. Subsequent landslides and debris flows occurred on April 30, May 2, and 3, 2016. Therefore, this study aims to examine the mechanism and to know the most significant contributing factor to the Beriti Hill landslide. Field investigation, soil sampling, XRD analysis, and Lidar analysis were carried out in the research. Beriti Hill is a geothermal area with many manifestations and is composed of volcanic rocks. Alteration processes produced a thick layer of soil from volcanic rocks. The thick soil dominated by clay minerals and steep slopes is the dominant controlling factor of a landslide, triggered by high rainfall intensity. Increasing water saturation in the landslide material due to high rainfall is the most contributing factor to the developing debris flow from the landslide. Debris flows are recurring events based on the Air Kotok river's stratigraphic data downstream of the landslide area. The debris flow material is toxic due to the low pH from the geothermal process. Therefore, the alluvial fan deposit area from Beriti Hill debris flow is a hazard zone and unsuitable for settlement and agriculture. This research shows that a landslide mechanism in a geothermal area was controlled by clay mineral presence due to the alteration process. The future of landslide risk assessment in the geothermal area can be considered by detailing clay type and their characteristic that significantly contributes to debris flow.
Keywords: landslides; geothermal; alteration; rainfall